Uhm Jung-hwa and the figure of new Korean woman - Wrochna, Agata Ewa (2021)
This thesis is an attempt to fill the gap in research present in contemporary South Korean (hereafter Korean) cinema studies in regards to the on-screen representations of modern Korean femininity. In particular, it focuses on the niche character of New Korean Woman, who is depicted as a reflection of the impending cultural and technological transformations of the country in the early 2000s and their influence on women. The figure avoids polarised representations of “good” and “bad” femininity – often present in contemporary Korean cinema partly due to the neo-Confucian legacy of the nation – and instead explores the concept of an individual choice as a decisive factor in a woman’s actions and societal role. The analysed case studies have been chosen from the filmography of accomplished and domestically recognised singer and actor Uhm Jung-hwa, who is here considered the pioneer and originator of the imagery associated with this particular type of cinematic heroine. Uhm and her film works have arguably been an important part of the last two decades of Korean film history. They raise issues crucial to modern women, especially those who seemingly reject the primary roles of wives, mothers and care takers imposed on them by society. The thesis additionally argues that the figure of New Korean Woman has been greatly conditioned by Uhm and her professional persona, first established prior to year 2000 on the music scene. Rather than erasing the existence of her celebrity experience, the thesis asserts that the examination of her film career through the context of her public image maintained outside the cinematic industry can significantly influence and enrich the audience’s perception of the protagonists represented by Uhm on the screen. On the other hand, Uhm’s establishing of such on- and off-screen ‘authenticity’ ensures the perception of her image as both familiar and extraordinary to the audiences following her career.